Pengembangan Sistem Informasi Pemesanan dan Reservasi Restoran Alam Kitchen Tulungagung Berbasis Website Menggunakan Metode Feature Driven Development (FDD) - Rafli Nur Gunawan; Taufiq Agung CahyonoCahyono; Agung Prasetya (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Alam Kitchen Restaurant in Tulungagung still uses a manual ordering and reservation process via telephone and WhatsApp, which causes risks of recording errors, service delays, and limitations in monitoring table availability in real time. This study aims to develop a website-based restaurant ordering and reservation information system and evaluate the feasibility of the resulting system. The study uses a Research and Development (R&D) method with a Feature Driven Development (FDD) approach that includes the stages of model design, feature identification, planning, design, and system feature development. Data collection was carried out through observation, interviews, and literature studies to identify user needs. System evaluation was carried out through functional testing using Black Box Testing and User Acceptance Testing (UAT) on 40 respondents. The test results showed that all system features run according to functional requirements, while the UAT results obtained a feasibility percentage of 85.75% with the category "Very Feasible". These findings indicate that the developed system is able to support the ordering process, table reservations, payment transactions, and restaurant data management in a more structured manner and improve service effectiveness compared to the previous manual system